2015
DOI: 10.1111/hpb.12383
|View full text |Cite
|
Sign up to set email alerts
|

Bile duct thrombi in hepatocellular carcinoma: is aggressive surgery worthwhile?

Abstract: The mere presence of BDTT in HCC does not indicate an advanced or inoperable lesion. When technically feasible, a formal hepatic resection is the preferred first-line treatment option in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Among 154 potentially relevant papers identified by the initial search, 20 finally met the inclusion criteria in this review and are summarised in Table 1 [ 3 9 , 12 26 ]. All studies were retrospectively designed, originated from Asia (Japan, n = 8 [ 5 , 6 , 12 , 13 , 15 , 20 , 21 , 25 ]; Mainland China, n = 7 [ 7 , 8 , 14 , 16 , 17 , 19 , 26 ]; Korea, n = 2 [ 18 , 22 ]; Taiwan, n = 1 [ 9 ]; India, n = 1 [ 23 ]; Hong Kong, n = 1 [ 24 ]) and classified as level-4 evidence. The sample size of each study varied from 13 to 73 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Among 154 potentially relevant papers identified by the initial search, 20 finally met the inclusion criteria in this review and are summarised in Table 1 [ 3 9 , 12 26 ]. All studies were retrospectively designed, originated from Asia (Japan, n = 8 [ 5 , 6 , 12 , 13 , 15 , 20 , 21 , 25 ]; Mainland China, n = 7 [ 7 , 8 , 14 , 16 , 17 , 19 , 26 ]; Korea, n = 2 [ 18 , 22 ]; Taiwan, n = 1 [ 9 ]; India, n = 1 [ 23 ]; Hong Kong, n = 1 [ 24 ]) and classified as level-4 evidence. The sample size of each study varied from 13 to 73 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found that the large lesions, capsule in ltration, poor differentiation, portal vein invasion and intrahepatic metastasis were more frequently observed in HCC patients with BDTT [5,18,19]. These differences suggested patients with BDTT had more particular in ltrative nature, which accounted for poorer prognosis than those without BDTT even after curative resection [7][8][9][18][19][20][21]. Since the bile duct and portal vein are encapsulated in the same Glissonian sheath, tumors can easily involve both of them.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative analysis of HCC with BDTT versus HCC without BDTT by Rammohan et al (21) indicated that the degree of preoperative jaundice and tumor size were important factors affecting prognosis. This result was consistent with the current finding that the degree of preoperative jaundice was the main factor influencing long-term survival (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%